2000
DOI: 10.22358/jafs/68053/2000
|View full text |Cite
|
Sign up to set email alerts
|

The response of turkeys to diets containing fat differing in degree of oxidation

Abstract: A 16-week experiment was conducted on 224 three-day-old BUT-9 turkey chickens randomly assigned to 4 groups, each with 4 replicates; each group comprised 7 toms and 7 hens. In successive 4-week periods the basic ration was supplemented with 2 to 5% of a mixture of rape seed oil and poultry fat (66:34) differing in peroxide value in groups I-IV <5, 50, 100 and 150 mEq 0 2 /kg, respectively.The addition of oxidized fat had a negative effect on the growth rate of turkeys, causing significant (PO.01) differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…In fact, it is reported that neither protein nor fat digestibility was affected by mildly oxidised oil . In contrast, there are some studies that report depressed growth and impaired health in birds fed oxidised oil Jacobsen et al, 1993;Sheehy et al, 1993;Engberg et al, 1996;Jankowski et al, 2000;Zdunczyk et al, 2002;Eder et al, 2003). In these studies, the detrimental effects of oxidised oil may be due to the administration of oils with high peroxide values or higher secondary lipid peroxidation products which have toxic effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is reported that neither protein nor fat digestibility was affected by mildly oxidised oil . In contrast, there are some studies that report depressed growth and impaired health in birds fed oxidised oil Jacobsen et al, 1993;Sheehy et al, 1993;Engberg et al, 1996;Jankowski et al, 2000;Zdunczyk et al, 2002;Eder et al, 2003). In these studies, the detrimental effects of oxidised oil may be due to the administration of oils with high peroxide values or higher secondary lipid peroxidation products which have toxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…The ingestion of oxidised oils also reduces tocopherol levels of tissues and plasma (Sheehy, 1993;Fei, 1995;Eder, 1999a;Jankowski et al, 2000) and increases the amount of thiobarbituric acid-reactive substances (TBARS), suggesting an elevation in lipid peroxidation and cellular fragility Sheehy et al, 1993;1994;Fei, 1995;Enberg et al, 1996;Eder & Kirchgessner, 1999;Juskiewicz et al, 2000). Similarly, Zdunczyk et al (2000) and Keller et al (2004) reported that oxidised dietary oils lead to a reduced antioxidant status of erythrocytes and make them more susceptible to haemolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: ryboflawinę, biotynę, kwas askorbinowy czy kwas pantotenowy (64). Ponadto wchodzi w interakcję z proteinami, tworząc nierozpuszczalne polimery obniżające przy-swajalność białek, eliminuje też witaminę E i selen (2,15,21,28). Następstwem jest dystrofia mięśnia sercowego i mięśni szkieletowych (52,53).…”
Section: Wykrywanie Tłuszczu Utlenionego W Paszyunclassified
“…Dodatkowo u ptaków dochodzi do pogorszenia się parametrów produkcyjnych (tj. nieśności i przyrostów dobowych masy ciała) oraz biochemicznych krwi, następuje też intensyfikacja zmian morfologicznych (9,28,31,34).…”
Section: Wykrywanie Tłuszczu Utlenionego W Paszyunclassified